ChemInform Abstract: [1, 2] Stevens Sigmatropic Rearrangement of Pyrrolidinium Ylides—Simple Synthesis of 3‐Aryl‐2‐cyano‐1‐methylpiperidines. Issue 19 (21st April 2016) - Kowalkowska, Anna; Jonczyk, Andrzej
Abstract: On treatment with a base, pyrrolidinium salts like (I) undergo ring expansion towards piperidines.